Progresivisme dan Rekonstruksionisme sebagai Paradigma Pendidikan untuk Transformasi Individu dan Masyarakat - Elsy Yulia Rahmani; Hermalia Putri Cahya Ramandhani; M. Yunus Abu Bakar (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
This journal highlight twoinfluential currents in educational philosophy: Progresivism and Reconstructionism. Progressivism emphasizes learning through experience,experimentation, and individual development. It views education as a process that should engage student in meaningful,real-world activites to cultivate critical thinking and creativity. Reconstructionism, on the other hand, positions education as a driving force for social change. It calls for questioning and reforming existing social stuctures and educational system to achieve greater equity and improvement. Together, these perspectives underscore the dynamic role of education in preparing learners not only for personal growth but also for active participation in transforming society.